(untitled) (Chemical Engineering Research Bulletin, 2010)
Reactive blends of polypropylene and unsaturated polyester with different compositions were prepared by melt processing using dicumyl peroxide (DCP) as initiator in a plasticoder. Rheological Characteristics of the blends were studied as a function of unsaturated polyester concentration over a range of strain rate. The possibility of forming a graft polymer increased with increasing the unsaturated polyester content. Change in viscosity behavior of the blends was a result of the competing reactions of degradation and grafting. Keywords: DCP; strain rate; degradation; grafting DOI = 10.3329/cerb.v14i2.5955 Chemical Engineering Research Bulletin 14 (2010) 105-108